2009
DOI: 10.1002/elan.200904667
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Behavior of Nitrazepam at a Screen‐Printed Carbon Electrode and Its Determination in Beverages by Adsorptive Stripping Voltammetry

Abstract: The cyclic voltammetric behavior of nitrazepam was investigated at screen-printed carbon electrodes over the range À 1.5 V to þ 1.5 V. Two reduction peaks were observable on the negative scan, at À 0.7 V, and À 1.2 V using pH 6 buffer. On the return scan a single oxidation peak was obtained at À 0.05 V. For quantitative analysis of beverages, we developed an anodic adsorptive stripping voltammetric method which required only dilution with buffer. The identification of nitrazepam and flunitrazepam could be achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…pharmaceuticals. Some pharmaceutical applications using this type of electrodes are: the quantitative analysis of paracetamol on an untreated screen-printed carbon electrode (SPCE) using amperometric detection coupled to a FIA system [13], the determination of lamotrigine by differential pulse adsorptive stripping voltammetry (DPAdSTV) using SPCE [14], and the electrochemical determination of nitrazepam at a SPCE using AdSV [15].…”
Section: Introductionmentioning
confidence: 99%
“…pharmaceuticals. Some pharmaceutical applications using this type of electrodes are: the quantitative analysis of paracetamol on an untreated screen-printed carbon electrode (SPCE) using amperometric detection coupled to a FIA system [13], the determination of lamotrigine by differential pulse adsorptive stripping voltammetry (DPAdSTV) using SPCE [14], and the electrochemical determination of nitrazepam at a SPCE using AdSV [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have expressed the need for miniaturisation of electrochemical setups and for the continuation of electroanalytical studies. 10 The ongoing pursuit within the electroanalytical eld using screen-printed electrodes is extremely diverse with many research groups applying these in a range of analytical pursuits allowing "in-eld" analysis where miniaturisation and portability can be realised. Other researchers such as Honeychurch et al 9 have focused upon analytes such as diazepam 9 and nitrazepam.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies we have shown that it was possible to use µL sample volumes for the determination of other benzodiazepines [28] and nitroaromatics compounds [35]. As it was our goal to apply these devices in the area of bioanalysis and forensic investigations, where the collection of large sample volumes can be problematic, we investigated the possibility of using a similar approach.…”
Section: Effect Of Sample Volumementioning
confidence: 99%
“…Recently, Martins et al [27] Previously, we have determined a variety of benzodiazepines using both screen-printed carbon electrodes (SPCEs) [28,29]. Consequently, we considered that it should be feasible to develop an electrochemical for the determination of clonazepam, using a SPCE.…”
Section: Introductionmentioning
confidence: 99%